2019
DOI: 10.17159/wsa/2019.v45.i3.6747
|View full text |Cite
|
Sign up to set email alerts
|

Review: Methods for the estimation of extreme rainfall events

Abstract: The estimation of design rainfalls is necessary to estimate the exceedance probabilities of extreme floods required to design hydraulic structures and to quantify the risk of failure of these structures. New approaches to estimating extreme rainfall events are being developed internationally. This paper reviews methods for estimating design rainfalls, particularly extreme events, in South Africa and internationally, and highlights the need to update methods used for estimating extreme rainfall events in South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Different statistical distributions and fitting methods are used in different countries, with the GEV distribution being the most common." A recent review paper emphasizes the PMP estimation in various countries(Johnson and Smithers 2019) including UK, US, Australia, and South Africa. The paper reviews in some detail the PMP estimation methods by WMO, the underlying uncertainties including climate variability and change, and suggest as a good practice to compare the PMP estimation based on alternative methods as well as the importance of updating periodically the design standards to include new data and knowledge because generally the estimated PMPs do not take into account recent extreme events Dyrrdal (2012).…”
mentioning
confidence: 99%
“…Different statistical distributions and fitting methods are used in different countries, with the GEV distribution being the most common." A recent review paper emphasizes the PMP estimation in various countries(Johnson and Smithers 2019) including UK, US, Australia, and South Africa. The paper reviews in some detail the PMP estimation methods by WMO, the underlying uncertainties including climate variability and change, and suggest as a good practice to compare the PMP estimation based on alternative methods as well as the importance of updating periodically the design standards to include new data and knowledge because generally the estimated PMPs do not take into account recent extreme events Dyrrdal (2012).…”
mentioning
confidence: 99%
“…Sedimentation management strategies include reservoir flushing, sediment bypass, and the construction of settling basins. Design flood estimation guidelines available from nine different countries are summarized in Table 3 based on some of the previous review articles [182,211,212]. For additional details, interested readers are referred to these articles and other references that are cited in this review.…”
Section: Guidelines and Bulletins On Design Flood Estimation And Dam ...mentioning
confidence: 99%
“…Solving the above equation provides the maximum likelihood estimates (MLE) θ = ( α, σ, μ). Numerous studies have shown EVT to successfully model extreme precipitation [41][42][43][44][45][46][47][48][49].…”
Section: Generalized Extreme Value Distributionmentioning
confidence: 99%